2011
DOI: 10.1039/c0cp02425b
|View full text |Cite
|
Sign up to set email alerts
|

Diffractive and reactive scattering of H2 from Ru(0001): experimental and theoretical study

Abstract: We present a combined experimental and theoretical study of the diffraction of H(2) from Ru(0001) in the incident energy range 78-150 meV, and a theoretical study of dissociative chemisorption of H(2) in the same system. Pronounced out-of-plane diffraction was observed in the whole energy range studied. The energy dependence of the elastic diffraction intensities was measured along the two main symmetry directions for a fixed parallel translational energy. The data were compared with quantum dynamics calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
84
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(101 citation statements)
references
References 59 publications
17
84
0
Order By: Relevance
“…63 It is noted here that the parameters describing the H 2 molecular beam differ somewhat from the parameters presented earlier, 30 as an error was made in the analysis of the TOF measurements. 63 …”
Section: Molecular Beamsmentioning
confidence: 71%
See 4 more Smart Citations
“…63 It is noted here that the parameters describing the H 2 molecular beam differ somewhat from the parameters presented earlier, 30 as an error was made in the analysis of the TOF measurements. 63 …”
Section: Molecular Beamsmentioning
confidence: 71%
“…Comparisons have also been made to experimental molecular beam studies on dissociative adsorption 31 as well as diffractive scattering. 30 The results of the comparison with experiments showed that neither functional could properly describe reaction over the entire interval of incidence energy, in the sense that the calculated reaction probability curve as a function of incidence energy was too narrow compared to the experimental curve, suggesting the energetic corrugation of the used potential energy surfaces to be too small. 30,31 The same semi-empirical mixture of these two functionals as the one which worked well for H 2 dissociation on Cu(111) 17,18 was also not able to describe the reaction probability of H 2 on Ru(0001) over the entire range of incidence energies.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations